A rare case of bladder paraganglioma treated successfully with robotic partial cystectomy - Kalyan M Shekhda; Jessal M Palan; Christo B Albor; Simon Wan; Teng-Teng Chung (Endocrine Oncology)
Bladder paragangliomas are rare extra-adrenal urological tumors that account for around 0.05% of bladder cancers. Their diagnosis is often delayed because of the rarity of these tumors. There is a risk of an intraoperative hypertensive crisis if not diagnosed or identified before surgical removal. We describe a case of a 36-year-old lady presented with a 10-year history of post-micturition palpitations and headaches. Her biochemical workup showed raised urinary normetanephrine levels and imaging showed a 123I MIBG-avid bladder mass compatible with bladder paraganglioma, although interestingly almost no tracer was picked up in 68Ga DOTATATE imaging. She was started on phenoxybenzamine to control her blood pressure prior to surgery. She underwent a successful robotic partial cystectomy with no complications. After surgery, she remained symptom-free. Bladder paragangliomas are rare neuroendocrine tumors of the bladder, which need to be diagnosed and managed effectively to avoid intraoperative and long-term complications.